1972
DOI: 10.1128/aem.23.5.951-952.1972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunogenicities of Chikungunya Vaccines Propagated in Monkey Kidney Monolayers and Chick Embryo Suspension Cultures

Abstract: A comparative study was made of Formalin-inactivated Chikungunya vaccines prepared from the virus propagated in African green monkey kidney monolayers and concentrated chick embryo suspension cultures. The vaccine prepared in the chick embryo suspension cultures was significantly more protective to mice against a live homologous virus challenge and stimulated the production of 4 to 5 times more circulating antibodies than the vaccine prepared with virus grown in African green monkey kidney monolayer cultures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1974
1974
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
(8 reference statements)
0
9
0
1
Order By: Relevance
“…No vaccine against chikungunya is currently available. The first attempts to develop an inactivated vaccine were reported at the end of the 1960s and involved detergent treatment of virus (White et al, 1972). Unfortunately, these formalin-killed vaccines which showed promise appeared to be moderately immunogenic and limited to short time effects in a clinical trial (Harrison et al, 1971).…”
Section: Vaccinesmentioning
confidence: 99%
“…No vaccine against chikungunya is currently available. The first attempts to develop an inactivated vaccine were reported at the end of the 1960s and involved detergent treatment of virus (White et al, 1972). Unfortunately, these formalin-killed vaccines which showed promise appeared to be moderately immunogenic and limited to short time effects in a clinical trial (Harrison et al, 1971).…”
Section: Vaccinesmentioning
confidence: 99%
“…challenge. Curiously, a separate study indicated that the CE preparation generated up to 5 times more antibody than the GMKC preparation (25). It was subsequently determined that the titer of the virus prior to formalin inactivation was critical for a potent immune response, with a highly concentrated product being necessary.…”
Section: History Of Chikv Vaccine Developmentmentioning
confidence: 99%
“…Vaccine – The first attempts to develop inactivated and attenuated vaccines against CHIKV resulted in products with low immunogenicity and adverse effects such as arthralgia ( Harrison et al, 1971 , White et al, 1972 ). Although some options are being evaluated, such as the use of recombinant antigens, viral-like particles, chimeric alphaviruses, electroporated DNA, and CHIKV attenuated by large-scale codon re-encoding, no vaccines are currently available ( Thiberville et al, 2013 ).…”
Section: Treatmentmentioning
confidence: 99%